2020
DOI: 10.1002/anie.201914743
|View full text |Cite
|
Sign up to set email alerts
|

A Robust, Precious‐Metal‐Free Dye‐Sensitized Photoanode for Water Oxidation: A Nanosecond‐Long Excited‐State Lifetime through a Prussian Blue Analogue

Abstract: Herein, we establish a simple synthetic strategy affording a heterogeneous, precious metal‐free, dye‐sensitized photoelectrode for water oxidation, which incorporates a Prussian blue (PB) structure for the sensitization of TiO2 and water oxidation catalysis. Our approach involves the use of a Fe(CN)5 bridging group not only as a cyanide precursor for the formation of a PB‐type structure but also as an electron shuttle between an organic chromophore and the catalytic center. The resulting hetero‐functional PB‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…A comparison of XPS profiles before and after mixing indicates that the binding energies of Zn 2p and Cr 2p exhibit slightly positive shifts after mixing [20] . Cobalt retains its +2 and +3 oxidation states, [35,43,44] whereas the amount of Fe 2+ ions in the mixed‐valent iron sites increases upon mixing suggesting an electron transfer from LDH to PBA structures (Figures 3 and S8), [27] which is in agreement with FTIR profile of LDH‐PB‐1 sample.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…A comparison of XPS profiles before and after mixing indicates that the binding energies of Zn 2p and Cr 2p exhibit slightly positive shifts after mixing [20] . Cobalt retains its +2 and +3 oxidation states, [35,43,44] whereas the amount of Fe 2+ ions in the mixed‐valent iron sites increases upon mixing suggesting an electron transfer from LDH to PBA structures (Figures 3 and S8), [27] which is in agreement with FTIR profile of LDH‐PB‐1 sample.…”
Section: Resultssupporting
confidence: 77%
“…Since they exhibit poor photocurrent efficiencies, the general strategy is to couple CoFe‐PBAs with suitable photosensitizers and semiconductors to utilize them for the light‐driven water oxidation process [27,32] . Herein, we prepare SC‐WOC hybrid assembly by coupling a CoFe‐PBA with a ZnCr‐LDH since i) they are precious metal free, ii) they can be prepared by straightforward solution chemistry, and iii) CoFe‐PBAs are projected to have a suitable band energy alignment that can facilitate charge transfer from the valence band of ZnCr‐LDH for the water oxidation reaction [33–36] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To expedite the electron dynamics in the photoanode/electrolyte interface, a WOC could be employed. Recently, many groups have explored the integration of a Prussian blue assembly with semiconductor and molecular chromophores . Overall, it was demonstrated that the addition of CoFe‐PBA as a WOC can significantly improve the carrier dynamics of the electrode, by mediating the water oxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, we developed a facial route based on oblique angle deposition to synthesize plasmonic nanostructures on a large scale. Moreover, we demonstrated that as a result of the cyanide chemistry, so‐called CoFe‐Prussian blue analog (PBA) is a strong and robust water oxidation catalyst (WOC), when connected to an organic chromophore . Inspired by these studies, herein, we adopt an extendable platform for the realization of a catalyst‐plasmonic architecture to improve the performance of semiconductor photoanodes with a facial and large‐scale compatible design in PEC‐WS.…”
Section: Introductionmentioning
confidence: 99%